Brief Report: Linking Depressive Symptoms to Viral Nonsuppression Among Women With HIV Through Adherence Self-Efficacy and ART Adherence. (1st April 2020) - Crockett, Kaylee B.; Entler, Kristin J.; Brodie, Emilee; Kempf, Mirjam-Colette; Konkle-Parker, Deborah; Wilson, Tracey E.; Tien, Phyllis C.; Wingood, Gina; Neilands, Torsten B.; Johnson, Mallory O.; Weiser, Sheri D.; Turan, Janet M.; et al.
Abstract : Background: Depression plays a key role in suboptimal HIV outcomes, possibly mediated by adherence self-efficacy beliefs and antiretroviral treatment (ART) adherence behavior. Applying social-cognitive theory, we examined a longitudinal sequential path model of the association between depressive symptoms and viral nonsuppression in women with HIV (WWH) through these mediating mechanisms. Methods: This was an observational longitudinal study using data from the Women's Adherence and Visit Engagement substudy of the Women's Interagency HIV Study. WWH (N = 375) completed measures of depressive symptoms, adherence self-efficacy, and ART adherence. Viral load was measured through blood draw. We examined a longitudinal sequential path model spanning 3 time points at least 6 months apart between 2015 and 2017. Indirect effects were assessed of depressive symptoms at time 1 (T1 ) on viral nonsuppression at T3 through adherence self-efficacy at T2 and ART adherence at T3 . Covariates included age, income, recreational drug use, race, and months on ART. Results: Depressive symptoms were associated with subsequent viral nonsuppression through its association with adherence self-efficacy and ART adherence [indirect effect: adjusted odds ratio = 1.004, 95% confidence interval: (1.001 to 1.008)]. Months on ART and recreational drug use were also significantly associated with viral nonsuppression at T3 . Conclusions: Our findings support depressive symptoms' association with adherence self-efficacy that in turn lead to suboptimal ART adherence and ultimately to viral nonsuppression for WWH. Tailoring of interventions aimed at addressing depressive symptoms, substance use, and adherence self-efficacy among WWH is needed to help close the gap between ART prescription and viral suppression on the HIV care continuum.